komposisi asam lemak dan asam amino kaldu tulang ayam - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
This experiment was conducted to extract nutrients from chicken frames and then analysed chemically the niârients from the broth especially fatty acid and amino acid profits. Frames of young broiler chickens and old b=oiler breeder chickens were used in this experiment. Half number of chicken frames was cut up and the other half one was minced. These two kinds of chicken frames were then cooked in a retort for certain length of time i.e. 27 minutes and 34 minutes. The broth of chicken frame was separated from its residue. It was then dried using freeze drier machine. The dried broth was analysed chemically especially to find out composition of fatty acid and amino acid. Ten fatty acids were found in the chicken broth. They were consisted of myristic, palmitic, palmitoleic, stearic, oleic, linoleic, linolenic, arakidic, eicosapentaenoic SPA and docosahexaenoic/DHA. However, there were only 5 major ones i.e. palmitic, palmitoleic, stearic, oleic and lir.,:qeic acids. Eighten amino acids were successfully identified in the broth i.e aspartic, thiamine, swine, glutandc, glycine, alanine, valine, isoleucine, leucine, phenylalanine, lysine, tyrosine, histidine, arginine, cystine, methionine, proline and hydroxyproline. Glycine, alanin, prolin and hydroxyprolin were the major amino acids in the broth which reflects the high collagen content of bone.